Revisiting Buddhist Economics: Contemporary Insights for Nepal - Pandey, Mukti Prasad (Prajñā Journal of Buddhist Studies, 2026)
The concept of Buddhist economics is emerged in the 20th century as an alternative economic philosophy. Derived from the teaching of the Buddha, it was developed by scholars seeking to address the negative externalities of capitalism and the free market system. Its practical application is evident in Bhutan's 'Gross National Happiness', Thailand's 'Sufficiency Economy' and the 'Santi Asoke Movement'. Unlike mainstream western economic principles; which emphasize profit maximization, increasing production and consumption, self-interest, and the notion that 'bigger is better'; Buddhist economics stresses the elimination of suffering, reduction of self-interest, minimization of consumption, work diligence, generosity, sustainable socio-economic development, and the well-beings of all sentient beings. This study examines the principles of Buddhist economics introduced by various scholars and their implementation across countries. It further explores their potential to address the challenges of an excessively exploitative market economy. Drawing on the original sources from the Pali cannon and secondary literature, including books, articles, and research reports, the study concludes that Buddhist economic thought remains highly relevant in the contemporary contexts. It provides viable responses to pressing issues such as resource overconsumption, social inequality, environmental degradation, and climate change. Adoption of these principles can promote inclusive and sustainable economic development, thereby contributing to peace and harmony within and among nations. The adaption of Buddhist economic concepts may contribute to supporting the Nepalese economy throughout the process of economic development.